Dominance of cyanobacteria in the composition of phytoplankton in a supply reservoir in the semiarid region of Ceará (Research, Society and Development, 2020)
Among aquatic organisms, microalgae deserve to be highlighted because they respond promptly to changes in water bodies. The present study aimed to understand the structure of the phytoplankton community in the Canoas reservoir, Ceará, Brazil, analyzing its relationship with environmental factors, in different periods (dry and rainy). Samples were collected monthly at three sampling points. The samples for analysis of the physical-chemical were obtained with the aid of a collection bottle of the Van Dorn type of 3.5 liters. For the quantification of phytoplankton, the samples were collected from the subsurface, fixed with lugol, analyzed and counted according to the Utermöhl method, using an inverted ZeissAxiovert microscope. Densities, dominant and abundant species, diversity index and equitability were determined. To test the significance between phytoplankton densities and environmental variables, the Shapiro-Wilk test and Pearson's correlation were used. Cyanophyceae showed the highest densities, especially the species of Cylindrospermopsis raciborskii and Pseudanabaena catenata, in both periods. Among the taxa, only two species were considered dominant and five were abundant. The phytoplankton community revealed a specific diversity considered low and the equitability showed a non-uniform distribution (66.6%), confirming the domain of few species. Some physical-chemical variables influenced the structure of the phytoplankton community, a significant correlation was observed (p